Giotto’s Circle – Example of Methodical Procedure for Early Detection/Encouragement of Preschools’ Giftednessfor Solvinglogically-Functional Mathematical Problems - Hilčenko, Slavoljub (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The aim of this paper is introduction of didactically-methodical procedure for early detection/encouragement of gifted children in solving problematically-logical and functional problems in math/geometry. We will display this procedure on the example of activities with preschool age group of children (6 years old), on which a new term is acquired – a CIRCLE. Problematical manipulative task called “Draw as correct circle as possible without using a divider”, which was conceptualized by the principles of “Nikola Tesla Center” (NTC) – MENSA of Serbia, was offered in three variants with different level of difficulty and number of didactical material for solving: 1) THE EASIEST PROCEDURE: with a logical block which has circle base + felt pen and paper, 2) MEDIUM-DIFFICULT PROCEDURE: pencil attached to the thread + paper and 3) THE MOST DIFFICULT PROCEDURE: color with brush + paper; Every child should make an individual attempt to solve all offered procedures – successively, one after the other, and their attempts, SUCCESS/FAILURES should be recorded by educator. Besides that, the paper indicates UNWILLINGNESS OF SERBIAN EDUCATION SYSTEM FOR THE GIFTED ONES = the necessary condition of the progress of every society, in which, they are LEFT ON THEIR OWN!.
Keywords: traditional education system ≠ early (UN) discovery of giftedness; an example of a workflow; didactics; methods; NTC + Mensa